Le conseiller pédagogique en tant qu'agent de changement : compétences et leadership transformationnel - Lachaîne, Claude; Duchesne, Claire (McGill Journal of Education, 2020)
Educational consultants participate in the implementation of Ministry of Education policies and those of their school board in matters of education in order to meet the needs of innovation, communication and collaboration of 21st century learners. Despite their pedagogical knowledge, their propensity for innovation and their interpersonal skills, however, they are unprepared to fulfill their position as an agent of change with their teaching colleagues. This article presents the results of research aimed at understanding the ways in which the transformational leadership of educational consultants is manifested in terms of their role as agents of change. Semistructured interviews with seven educational consultants and four directors of pedagogical services from four Frenchlanguage school boards in Ontario revealed links between the skills they mobilize to guide teachers towards a change in practice and the manifestations of transformational leadership as developed by Bass (1998).